2009
DOI: 10.1080/13102818.2009.10818441
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of the Protected Resurection SpeciesRamonda SerbicaPanč.—Habitat Montana District, Bulgaria asIn Vitro, Plants Through a Modified Micropropagation System

Abstract: Ramonda serbica Panč. is a rare species, Balkan endemic and tertiary relict, included in the European list of rare, in danger of extinction and endemic plants. It is also included in the Bulgarian list of endangered plants. In Bulgaria, this species has not been cultivated in vitro with the aim of conservation and investigation of the natural population. For this purpose, at the Plant Biotechnology laboratory at the University of Plovdiv we started the establishment of a live collection of in vitro Ramonda ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…It appears that the phytohormones are not necessary for seed germination medium for oligotrophic seeds of Ramonda plants. The same results were obtained from the experiments carried out with R. serbica seeds of Bulgarian area (Dontcheva et al 2009;Daskalova et al 2012). The authors have observed a normal organogenesis of individual plantlets from germinated seeds in the nutrient medium GM without sugar and phytohormones.…”
Section: Direct Organogenesis Stage 1 (Seed Germination)supporting
confidence: 77%
“…It appears that the phytohormones are not necessary for seed germination medium for oligotrophic seeds of Ramonda plants. The same results were obtained from the experiments carried out with R. serbica seeds of Bulgarian area (Dontcheva et al 2009;Daskalova et al 2012). The authors have observed a normal organogenesis of individual plantlets from germinated seeds in the nutrient medium GM without sugar and phytohormones.…”
Section: Direct Organogenesis Stage 1 (Seed Germination)supporting
confidence: 77%
“…Previous investigation of R. serbica and R. nathaliae has brought the evidence to adaptive features necessary to preserve cell membrane integrity (Quartacci et al 2002), antioxidative capacity (Sgherri et al 2004;Jovanoviç et al 2011), photosynthetic activity (Tuba et al 1998), CO 2 fixation and chlorophyll a fluorescence (Degl'Innocenti et al 2008), genome size variation and polyploidy (Siljak-Yakovlev et al 2008), osmotic adjustment (Zivkoviç et al 2005), seed germination (Gashi et al 2012a) and in vitro cultivation from seeds of Ramonda plants (Kongjika et al 2002;Gashi et al 2011;Dontcheva et al 2009;Daskalova et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…This research has brought the evidence of adaptive features necessary to preserve cell membrane integrity [4], antioxidative capacity [5,6], photosynthetic activity [1], CO 2 fixation and chlorophyll a fluorescence [7], genome size variation and polyploidy [8], osmotic adjustment [9], seed germination [10] and in vitro cultivation from seeds of Ramonda plants [11][12][13].…”
Section: Introductionmentioning
confidence: 99%